Exploring the dynamic impact of future land use changes on urban flood disasters: A case study in Zhengzhou City, China - Yuanyuan Bai; Shao Sun; Yingjun Xu; Yi Zhao; Yujie Pan; Yao Xiao; Ruoxin Li (Geography and Sustainability)
In recent years, urban floods have increased in frequency and severity due to intensified extreme rainfall events exacerbated by rapid urbanization. This study integrates a Markov-PLUS model and a rainfall-runoff-flood hydraulic numerical model to establish a scenario-based research framework for identifying interactions between land use dynamics and urban flood risk, using the Jialu River basin in Zhengzhou, China, as a case study. Future land use changes under three scenarios were forecast: Natural Development (ND), Economic Development (ED), and Ecological Protection (EP), alongside rainfall scenarios occurring every 10, 50, and 100 years. There were expansions and decreases in construction land under the ED and EP scenarios, respectively, emphasizing the importance of prioritizing ecological conservation. Economic scenarios showed the highest risks under the increased surface runoff and flood risk driven by higher rainstorm intensity. Over the next 15 years, the Economic Development scenario is projected to increase flood hazard areas, whereas the intensified Ecological Protection scenario is expected to reduce these risks. This underscores the contribution of prioritizing ecological conservation to mitigating disaster risks, calling for enhanced drainage systems and elevated flood protection standards to promote resilient urban development in the face of increasingly severe urban flood challenges.